Altered Baseline of Plasma Glucagon Level in pre-Obese to very Obese Persons - Lesmana, Ronny; Mulyanaga, William Giovanni; Mukarromah, Siti Baitul; Goenawan, Hanna; Darmayanti, Meita; sugianli, Adhi (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
â€œBihormonal hypothesisâ€ is disturbances of both insulin and glucagon in diabetes mellitus. It resulted in a high blood glucose level. Interestingly, as one of Diabetes Mellitusâ€™s risk factors and metabolic disorders, obesity may also play role in altering homeostasis and regulation of glucose metabolism in blood and its utilization in tissues. Unfortunately, there is limited information about the alteration of glucagon levels in various degrees of obesity. This research objective is to learn the plasma glucagon levels alteration in pre-obese, obese, and very obese persons in Jatinangor in 2015. We had observed 31 obese female subjects in one village. This study was conducted using descriptive quantitative with cross-sectional design. Blood vein samples from the left arm were collected, stored, and transferred to Dr.Hasan Sadikin General Hospital. Glucagon plasma was measured by the ELISA method. We discovered an interesting pattern that showed a correlation between glucose level and the glucagon level in a very obese group. We observed average glucose level is declined and linearly associate with the glucagon level from pre obese to obese and to very obese group. The average level of glucagon in the pre-obese group is 158.62 pg/mL, the obese group is 149.99 pg/mL, and the very obese group is 111.98 pg/mL.